2016
DOI: 10.1111/jfd.12505
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Aeromonas salmonicida in fish tissue by real‐time PCR

Abstract: Furunculosis, a septicaemic infection caused by the bacterium Aeromonas salmonicida subsp. salmonicida, currently causes problems in Danish seawater rainbow trout production. Detection has mainly been achieved by bacterial culture, but more rapid and sensitive methods are needed. A previously developed real-time PCR assay targeting the plasmid encoded aopP gene of A. salmonicida was, in parallel with culturing, used for the examination of five organs of 40 fish from Danish freshwater and seawater farms. Real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Indeed, such Aeromonas species could be well adapted to a estuarine environment having a cooler surface water with mean temperature of 13.4°C (min: 5.3°C/ max 21.3°C). Except for A. salmonicida (Henriques et al, 2006), these species, previously observed in farmed fishes (water and fish) (Esteve et al, 1995; Schmidt et al, 2001; Hatha et al, 2005; Behbahani et al, 2014; Bartkova et al, 2016) and in waste water (Figueira et al, 2011; Marti and Balcázar, 2015; Popovic et al, 2015; Vaz-Moreira et al, 2015; Varela et al, 2016), have never been, as far as we know, described in coastal and anthropized estuary waters. Only the species A. hydrophila , A. caviae , A. sobria , and A. veronii have been reported in coastal or estuarine environments (the Adriatic Sea, Italy) (Dumontet et al, 1996; Fiorentini et al, 1998; Gugliandolo et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, such Aeromonas species could be well adapted to a estuarine environment having a cooler surface water with mean temperature of 13.4°C (min: 5.3°C/ max 21.3°C). Except for A. salmonicida (Henriques et al, 2006), these species, previously observed in farmed fishes (water and fish) (Esteve et al, 1995; Schmidt et al, 2001; Hatha et al, 2005; Behbahani et al, 2014; Bartkova et al, 2016) and in waste water (Figueira et al, 2011; Marti and Balcázar, 2015; Popovic et al, 2015; Vaz-Moreira et al, 2015; Varela et al, 2016), have never been, as far as we know, described in coastal and anthropized estuary waters. Only the species A. hydrophila , A. caviae , A. sobria , and A. veronii have been reported in coastal or estuarine environments (the Adriatic Sea, Italy) (Dumontet et al, 1996; Fiorentini et al, 1998; Gugliandolo et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Molecular methods with their high sensitivity and specificity have become the favoured options in many laboratories for the diagnosis of fish diseases (e.g. Abu-Elala et al 2015; Bartkova et al 2017;Fernandez-Alvarez et al 2016;Keeling et al 2013;Mooney et al 1995;. Techniques capable of detecting virtually single cells have been described.…”
Section: Culture-independent Methods-molecular Biologymentioning
confidence: 99%
“…Re-challenge of survivors would also confirm the pathogenfree status. A. salmonicida has been found in the gut and brain of asymptomatic carrier fish 51 suggesting that a low number of pathogens are kept at distance by the innate (SAA, C3, cathelicidins, lysozyme) and adaptive (IgM) immune genes activated in the resistant surviving fish.…”
Section: Discussionmentioning
confidence: 99%